Influência de mensagens de texto na colaboração de pacientes jovens com o tratamento ortodôntico - Costa, Pedro Augusto (2017)
The aim of this study was to investigate the influence of a digital application (app) designed for social communication in young patient compliance within orthodontic treatment. A sample of 54 young patients under orthodontic treatment (28 males and 26 females), aged between 11 and 23.7 years old (mean age: 14.7 years) was divided in two groups of 27 (experimental and control groups). Weekly text messages were sent to the experimental group during 4 months through a digital application designed for social communication, for avoiding brackets and tubes failures in the first 4 months of treatment. After the evaluation period, the number of failures were compared between the groups. Fisher’s exact test was used to compare the number of patients with at least one failure. Chi-square test was used to compare the quantity of failures between the groups. Spearman correlation coefficient was applied to associate the quantity of failures with the age of the patients sampled. For comparisons between males and females considering the quantity of brackets failures, the parametric Mann-Whitney test was used. All the statistic tests were performed with a significance rate set in 5% (p<0.05). Experimental and control groups did not reach statistically significant differences concerning the quantity of brackets failures. This study concluded that Text messaging through the digital application was not able to influence considerably in the quantity of brackets failures in early stages of orthodontic treatment.